IMPLEMENTASI PEMBELAJARAN ILMU TAJWID MENGGUNAKAN KITAB HIDAYATUL MUSTAFID UNTUK MENINGKATKAN KUALITAS MEMBACA AL-QUR’AN SANTRI TINGKAT I’DADIYAH - Mursyidah, Nurul; Gustiawati, Syarifah; Muhlisin, Sofian (An Nuqud Journal of Islamic Economics, 2025)
This study aims to describe the implementation of tajwid (Qur’anic recitation rules) instruction using the Hidayatul Mustafid book to improve the Qur’an reading quality of I’dadiyah-level students at Pondok Pesantren Nur Azkia Bogor. The background of this research is based on the importance of mastering tajwid to preserve the authenticity of Qur’anic recitation and the need for effective teaching methods for beginner students. This research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results indicate that the tajwid learning process using the Hidayatul Mustafid book is carried out systematically through lectures, dictation, and question-and-answer sessions, supported by translations in Arab Pegon and the use of local languages. The book is considered effective due to its concise, systematic, and easy-to-understand content. Despite challenges such as limited understanding of classical Arabic and students’ motivation, learning success is achieved through the active role of instructors, contextual teaching strategies, and student enthusiasm. The conclusion of this study is that Hidayatul Mustafid is effective in enhancing students’ understanding and Qur’an reading skills, and it can serve as a relevant model for tajwid instruction in the modern era